2014
DOI: 10.1039/c3ja50371b
|View full text |Cite
|
Sign up to set email alerts
|

Relative spectral response calibration of a spectrometer system for laser induced breakdown spectroscopy using the argon branching ratio method

Abstract: This paper reports the use of the Ar branching ratio as an alternative means of calibrating the relative spectral response of a spectrometer/detector apparatus, with emphasis on its use in Laser Induced Breakdown Spectroscopy (LIBS) diagnostic experiments. The method is compared to the more conventional calibration routine using standard lamps. The argon method was implemented with an Ar-filled hollow cathode lamp and with a LIBS plasma in argon at different pressures. For the conventional calibration, a quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…As an alternative and easy-to-implement way of calibrating the response, Li et al 101 reported the use of the wellknown Ar branching ratio. Quartz tungsten halogen lamps are widely used as spectral irradiance and radiance standards due to their continuous smooth emission from 250 to 2400 nm.…”
Section: Libsmentioning
confidence: 99%
“…As an alternative and easy-to-implement way of calibrating the response, Li et al 101 reported the use of the wellknown Ar branching ratio. Quartz tungsten halogen lamps are widely used as spectral irradiance and radiance standards due to their continuous smooth emission from 250 to 2400 nm.…”
Section: Libsmentioning
confidence: 99%
“…However, these devices call for expensive recalibration aer a certain number of working hours. As an alternative and easy-to-implement way of calibrating the response, Li et al 101 reported the use of the wellknown Ar branching ratio. They showed that this method, in a laser-induced argon plasma, provided results tting well (e.g.…”
Section: Libsmentioning
confidence: 99%
“…Second, the rovibrational intensity distribution of NO and N 2 molecular emission from a low-temperature radio-frequency discharge plasma is used to correct the apparatus response function. A correction method based on a laser-induced plasma was proposed by Li et al [16]. Generating breakdown in argon gas, the emission of lines from the same upper energy level of Ar and Ar + species was used for calibration.…”
Section: Introductionmentioning
confidence: 99%